Genetically modified soybeans in animal feed : commercial actors’ ethical perspective in the Swedish market - Danielsson, Theodor; Gerhardsson, Per (SLU/Dept. of Economics, 2017)
The world’s population is increasing, thus the need for food as well. As a result, innovation is needed in the agriculture sector to increase the production of food. Genetically modified, GM, crops could be such an innovation. However, with the use of GM crops today, some disadvantages have led to that the European Union have banned GM crops in cultivation within the union. Nevertheless, the EU imports a significant amount of GM crops from other parts of the world, such as Brazil, to use in animal feed, especially GM soybeans due to the high protein content. Sweden is the one country within the union that only imports GM-free soybeans due to a joint agreement among commercial actors.